Needs Analysis: Strategic Issue on the Teaching of English for Specific Purposes for the Study of Sciences and Technology - Lubna Algadrie (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
With the development of science and technology scholars and professionals now need to acquire a higher form of literacy to be able to participate in groups of similar fields or groups of works. The need for English as one of the International language, an established language, has increased because English has access to world knowledge particularly in the field of science and technology, computer utilization, international trade and commerce. However, the need can vary in terms of the study fields, selection of skills, selection of language functions, and the language learners. Effective strategies can only be applied through a thorough analysis of the learners needs, which will refer to the whole range of language resources for material selection. Since it is clear that ESP course is directly concerned with the purposes of which the learners need English, ESP course should be learner-centered. In this paper the writer would like to give the results of needs analysis (wants and strategies: Shaw, 1982, Allwright and Allwright, 1997) done among the learners (students and lecturers of engineering studies from various departments) of Institut Teknologi Sepuluh Nopember Surabaya (ITS) who are learning English at ITS Language Center to fulfill the market demand for job employment of their career and further studies.